On frogs, toxins and true friendship: an atypical case report. Issue 1 (December 2016) - Daniel-Ribeiro, Cláudio; Roussilhon, Christian
Abstract The authors report a series of events including the scientific interest for poisonous dendrobates of French Guiana, the human confrontation with the immensity of the evergreen rainforest, the fragility of the best-prepared individuals to a rough life, and the unique and very special manifestation of a solid friendship between two experts and enthusiasts of outdoor life. In the evergreen forest of South America, as in many other scientific field expeditions, everything may suddenly go wrong, and nothing can prepare researchers to accidents that may occur in a succession of uncontrollable errors once the first mistake is done. This is what happened during an expedition in search for dendrobates by an experienced forest guide and naturalist. The authors decided to report the story, considering that it deserved to be brought to the attention of those interested in venomous animals and toxins, in order to illustrate the potential danger of dealing with these organisms.